Emotion Management Ability - Kluemper, Donald H.; DeGroot, Timothy; Choi, Sungwon (Journal of Management, 2013)
This article examines emotion management ability (EMA) as a theoretically relevant predictor of job performance. The authors argue that EMA predicts task performance, organizational citizenship behavior (OCB), and workplace deviance behavior. Moreover, to be practically meaningful, managing emotions should predict these important organizational outcomes after accounting for the effects of general mental ability and the Big Five personality traits. Two studies of job incumbents show that EMA consistently demonstrates incremental validity and is the strongest relative predictor of task performance, individually directed OCB, and individually directed and objectively measured deviance.